Protocol for the development of a consensus practice guideline To address clinical and regulatory barriers to buprenorphine dispensing in community pharmacy - Tyler J. Varisco; Hannah Fish; Joshua Bolin; David Dadiomov; Lucas G. Hill; Ekere J. Essien; Matthew A. Wanat; Diane Ginsburg; Jeanne Waggener; Sahar Yazdanfard; Juhyeon Song; Whanhui Chi; et al. (BMC, 2024)
Abstract Background Less than half of community pharmacies in the United States stock buprenorphine products indicated for the treatment of opioid use disorder. This lack of access to buprenorphine in community pharmacies is a significant barrier to care. To address this issue, this protocol outlines a comprehensive approach to develop a practice guideline aimed at improving access to safe and effective opioid use disorder treatment in community pharmacies. Methods The guideline development process will proceed in three phases, following a technique closely aligned with the Institute of Medicine's guidance on guideline development. The first phase will involve conducting qualitative interviews with pharmacists in three states to identify their beliefs toward buprenorphine dispensing. As limitations on buprenorphine supply are related to constraints at all levels of the drug supply and regulatory system, the second phase, we will recruit representatives from regulatory agencies, pharmacy organizations, the Drug Enforcement Administration, pharmaceutical wholesalers as well as addiction medicine physicians and psychiatric pharmacists to develop consensus recommendations through a modified Delphi design. This will be followed by a public comment period and external expert review of the recommendations led by the National Association of Boards of Pharmacy. Finally, in the third phase, a national, mixed media dissemination campaign will be led by the National Community Pharmacists Association (NCPA) to convey recommendations to practicing pharmacists. Discussion The guideline development process aims to incorporate the perspectives of multiple stakeholders and emphasize the importance of addressing the regulatory and pharmacy-specific aspects of care in addition to clinical evidence and guidance. The development of this guideline will provide targeted, multidisciplinary guidance for pharmacists, improving access to safe and effective opioid use disorder treatment in the community setting. Preregistration This protocol was registered with the Open Science Framework in March of 2023. Registration may be found at: https://doi.org/10.17605/OSF.IO/6S9DY .